PENGARUH STRATEGI PEMBELAJARAN AKTIF TERHADAP PRESTASI BELAJAR SISWA DI SDN TEGALURUNG 2 KECAMATAN BALONGAN INDRAMAYU:Studi Deskriptif Pada Siswa Kelas IV SDN Tegalurung 2 Kecamatan Balongan Indramayu Dalam Program DBE 2 USAID - PRADANA, Ferdy (2012)
The problem of this study is "How does an idea of the effect of active learning strategies on student achievement in SDN Tegalurung 2 District Balongan Indramayu"?. The goal: 1) To determine a general active learning strategies in SDN Tegalurung 2 Balongan Indramayu District, 2) To know the general picture of student achievement in SDN Tegalurung 2 District Balongan Indramayu, 3) To determine the effect of active learning strategies on student achievement in SDN Tegalurung 2 District Balongan Indramayu. This study rests on the concept: 1) active learning strategies, 2) student achievement. The research method used in this study is quasi-experimental method by using a quantitative approach. The population in this sample is a class IV SDN Tegalurung 2 District Balongan Indramayu. Pengembilan samples was done by using an experimental class, and therefore the sample used is a class IV SDN Tegalurung 2 District Balongan Indramayu. The data analysis technique used is a validity test, reliability test, homogeneity test variants, test hypotheses. Based on the results of data processing result that: 1) An overview of active learning strategies in SDN Tegalurung 2 District Balongan Indramayu very well, it is seen from the average value of 4,35 was the criterion very well, 2) overview of student achievement SDN Tegalurung 2 Balongan Indramayu district is divided into two parts, namely, student achievement pretest average is 8,87. While student achievement posttest average value 16,57. This shows that the level of student achievement before and after the learning of learning increases, 3) active learning strategies affect student achievement in SDN Tegalurung 2 District Balongan Indramayu moderately (0,424) and the determination of 18,4%. It is evident from the findings and discussion of research that shows that the test based on the class of experimental tests of student achievement before and after treatment were significantly increased as well as the regression test showed a linear equation.